Simple and Accurate HPTLC-Densitometric Method for Assay of Nandrolone Decanoate in Pharmaceutical Formulation - Dołowy, Małgorzata; Pyka-Pająk, Alina; Jampílek, Josef (Molecules, 2019)
This study reports the development and validation of a new, simple, and accurate high-performance thin-layer chromatography (HPTLC)-densitomeric method for the determination of nandrolone decanoate in a commercially available injection formulation. Chromatographic analysis was performed on glass CN modified silica gel 60F254 plates developed using n-hexane-ethyl acetate in volume ratio 42.5:7.5 as the mobile phase. Densitometric scanning was carried out at the wavelength of 245 nm. This chromatographic system gave compact spot and a symmetrical peak of nandrolone decanoate with retardation factor (RF) value at 0.57 (±0.02). The linearity of this method with the high correlation coefficient of calibration plot ranges from 0.780 to 12.500 μg/spot. The developed method is characterized by good precision (coefficient of variation CV < 2%) and high accuracy close to 100.3% (R = 99.0%). Values of limits of detection and quantification equal to 0.231 and 0.700 μg/spot, respectively, confirm the sensitivity of the developed method. The analysis of the pharmaceutical formulation of nandrolone decanoate indicates drug content of 50.5 mg/mL and 101.0% in relation to the label claim. This is in good agreement with the recommendation of the International Council for Harmonisation (ICH) guidelines as well as the pharmacopoeial requirements. The low CV value (<1%) of nandrolone decanoate content in the tested injection formulation confirms the suitability of the proposed HPTLC-densitometric method for routine control of this compound in examined pharmaceuticals.
Keywords: léčivé přípravky; Nandrolone Decanoate; Reproducibility of Results; nandrolon dekanoát; vysokoúčinná kapalinová chromatografie; příprava léků; chromatografie na tenké vrstvě; denzitometrie; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; Chromatography, Thin Layer; Drug Compounding; Sensitivity and Specificity; Pharmaceutical Preparations; Densitometry; senzitivita a specificita